Improved Oral Hygine as A Result of Successful Toothbrushing Intervention in a Restricted Community Islamic Boarding School (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Brushing teeth is an important thing to do since it is one of the factors that affect oral hygiene,especially to remove plaque on the teeth.1 The ability to brush teeth properly and correctly is a fairly importantfactor in maintaining dental and oral health, especially in adolescence.5 The purpose of study to explain thedifferences in plaque scores before and after toothbrushing training using Bass technique in adolescentsMethod: The sample were 100 students aged 12-15 years old in grades 7, 8 and 9. This study design wasexperimental quasi and using a pre-test and post-test after 7 days to determine the difference in plaque scoresbefore and after the training. The plaque index method that used to examine oral hygine was Patient HygienePerformance (PHP). Comparison between plaque scores before and after training evaluated using Wilcoxontest. Result: Examination of PHP index before training shows 81 samples (81%) in poor criteria, thenmost subjects undergoes improvement after training. There were 94 samples (94%) experienced decreaseor improvement in plaque score whilst 6 samples (6%) did not show improvement after training. Medianof plaque score before training was 4.3 (0.2-5 (SD=0.502)) afterwards improved to 2.2 (0-4.8 (SD=0.496)).Wilcoxon test obtained a value of p
Keywords: dental plaque, toothbrush, bass technique, oral hygiene